Transnational Data Flow Constraints: A New Challenge for Multinational Corporations - Samiee, Saeed (Journal of International Business Studies, 1984)
This article examines the implications of transnational data flow constraints for international business. The need for a free flow of information across national boundaries—facilitating international business and reducing costs for multinational corporations—is discussed. Although both large and small firms are affected by transnational data constraints, companies that are managed in a decentralized fashion are affected to a lesser degree. Economic protectionism has emerged as a major reason for regulating transnational data flow by nation states.